AN ANALYSIS OF STUDENTS' TRANSLATION WORKS OF A BARACK OBAMA'S POLITICAL SPEECH - Nur'azizah, Wulan (2015)
This study focused on analyzing the translation strategies used by the students in translating a political speech of Barack Obama, the difficulties faced by them in translating it and the quality of the translation works. This study used a descriptive-qualitative method with document analysis technique, using the theory of translation strategy proposed by Vinay & Darbelnet (in Fawcett, 1997, pp. 34-9; in Bell, 1991, pp. 70-71) and Newmark (1988). This study also used the NAATI's assessment method to find out the quality of students' translation works. The main data of this study were the students' translation work of translation students in 8th semester. The findings showed that the students employ nine translating strategies in dealing with the text, there were transposition (49,33%), reduction (14,66), expansion (6,66%), literal/word for word (5%), paraphrase (3,66%), naturalization (3,33%), equivalence (3%), couplets (2,66%), and calque (1,33%). However it was also found some cases mistranslation which reached 10,33%. While in terms of difficulties faced by the students in translating a text, it was done by examining vocabulary problem, lexical problem, and syntactic problem. In terms of students' translation quality, it was found that two of three participants were judged as acceptable translation while the other one was unacceptable. It can be concluded that the students employ several strategies in translating a political speech and the problem faced by them was complicated since political speech was contained sophisticated words and unfamiliar diction, therefore it was affecting the quality of the translation works. Keywords: Students translation works, translation Strategies, translation difficulties, translation quality, political speech. Penelitian ini fokus kepada analisi strategi penerjemahan yang digunakan mahasiswa dalam menerjemah pidato politik Barack Obama, kesulitan yang dihadapi saat menerjemah dan kualitas dari penerjemahan tersebut. Penelitian inii menggunakan metodologi deskriptif-kualitatif dengan teknik menganalisis dokumen, menggunakan teori strategi penerjemah dari Vinay & Darbelnet dan Newmark. Penelitian ini juga menggunakan metodologi penilaian NAATI untuk mengetahui kualitas hasil penerjemahan mahasiswa di semester ke 8. Penemuan menunjukan bahwa mahasiswa menggunakan sembilan strategi penerjemahan, yaitu transposition (49,33%), reduction (14,66), expansion (6,66%), literal/word for word (5%), paraphrase (3,66%), naturalization (3,33%), equivalence (3%), couplets (2,66%), dan calque (1,33%). Walaupun demikian masih terdapat mistranslation sebanyak 10,33%. Dalam hal kesulitan yang dihadapi oleh mahasiswa, diteliti dengan memeriksa permasalahan kosa kata, permasalahan leksikal, dan permasalahan sintaksis. Dalam hal kualitas penerjemahan mahasiswa, ditemukan dua dari tiga partisipan ditetapkan sebagai penerjemahan yang diterima sedangkan satu lainnya tidak. Dapat disimpulkan, mahasiswa menggunakan beberapa strategi dalam menerjemahkan pidato politik dan kesulitan yang dihadapi cukup rumit mengingat pidato politik memuat kata-kata yang mutakhir dan diksi yang tidak familiar, sehingga mempengaruhi kualitas dari hasil penerjemahan. Kata kunci : hasil penerjemahan mahasiswa, strategi penerjemahan, kesulitan penerjemahan, kualitas penerjemahan, pidato politik.